Cancer survivors’ self-efficacy to self-manage in the year following primary treatment - Foster, Claire; Breckons, Matthew; Cotterell, P.; Barbosa, D.; Calman, Lynn; Corner, Jessica; Fenlon, Deborah; Foster, R.; Grimmett, Chloe; Richardson, Alison; Smith, P.W. (Springer, 2014)
PURPOSE Cancer survivors are increasingly expected to manage the consequences of cancer and its treatment for themselves. There is evidence that self-efficacy is important for successful self-management and that this can be enhanced with support. The purpose of this study was to assess self-efficacy to manage problems in the year following primary treatment.